Dioecy and wind pollination in Pernettya rigida (Ericaceae) of the Juan Fernández Islands - Anderson, Gregory J. (2000)
Pernettya rigida is endemic to the Juan Fernández archipelago. Although all flowers are complete, with seemingly fertile stamens and pistils, differences in fruit production and detailed field, anatomical, and morphological studies indicate they are functionally unisexual, and the species is consequently dioecious. A comparison of 15 features demonstrated significant differences between the sexes. The populational sex ratio is 1:1. Nectaries located between the filaments produce small amounts of floral nectar with similar sugar composition in both sexes. There are x=33,357 (or x=133,429) pollen tetrads (or pollen grains)/male flower and x=109 ovules/female flower. No tetrads in either hand self-pollinated or open pollinated male flowers showed any pollen germination. Tetrads on open- and hand-pollinated female flowers germinate. Female flowers do not show autogamy or apomixis. During more than 80 hours of field observation, we recorded only seven floral visitors (representing three insect species). In spite of this, open-pollinated female flowers have abundant fruit and seed-set. Thus, we conclude that pollen is transferred abiotically and the ever-present wind over the exposed ridges of the islands is the likely dispersal agent. A number of anemophilous features, such as dry pollen and exposed habitat, support this conclusion. Thus, dioecy and anemophily have evolved independently, in situ, in this species in this remote locality. Preservation of habitat and elimination of competitive invasives are the primary conservation challenges.